2011
DOI: 10.1007/s12570-011-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain in patients with osteoarthritis of hip joint

Abstract: Objectives The aim of the present study was to evaluate the relationship between neuropathic pain and pain deriving from osteoarthritis of the hip joint, using painDETECT, a self-report questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Shirai et al [28] stated that hip pain occurs following the invasion of the labrum with blood vessels and nerve fibers from inflamed synovial tissue following labral degeneration in the hip joint affected by OA. Shigemura et al [2] reported that 6% of patients with OA of the hip showed neuropathic pain. These find-ings may provide the development of novel analgesic therapies for hip joint pain including the treatments targeting NGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shirai et al [28] stated that hip pain occurs following the invasion of the labrum with blood vessels and nerve fibers from inflamed synovial tissue following labral degeneration in the hip joint affected by OA. Shigemura et al [2] reported that 6% of patients with OA of the hip showed neuropathic pain. These find-ings may provide the development of novel analgesic therapies for hip joint pain including the treatments targeting NGF.…”
Section: Discussionmentioning
confidence: 99%
“…However, referred pain may occur in osteoarthritis (OA) [1][2], osteonecrosis [3][4], acetabular labral lesion [5], and other hip disorders. Pain has been reported to affect the thigh or lower leg as well as the hip itself.…”
Section: Introductionmentioning
confidence: 99%
“…No previous studies are available on the correlation between mPDQ and the VAS pain or subscales of KOOS/HOOS and RAND-36. However, some results are available for the correlation between the PDQ (unmodified), VAS pain and subscales of the RAND-36, reporting correlations between VAS pain and PDQ of 0.39, and of 0.53 in hip and knee OA patients [20,46]. A correlation of 0.30 between PDQ and the RAND-36 pain subscale was previously described [42].…”
Section: Construct Validitymentioning
confidence: 93%
“…In hip OA, up to 19% of the patients and in knee OA 19-37% of the patients experience possible or likely neuropathic pain [3,[19][20][21][22][23]. Besides clinical assessment by specialised pain physicians and elaborate protocols for physical examination for neuropathic symptoms [quantitative sensory testing, (QST)], several questionnaires are available to distinguish neuropathic pain symptoms from nociceptive pain symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a common chronic degenerative disease characterized by loss of articular cartilage . Major clinical signs of hip OA are groin pain with weight bearing, restricted range of motion, and gait disturbance, which deteriorates the quality of life of affected individuals. Referred pain may occur in OA.…”
mentioning
confidence: 99%